Exploratory approach utilising virtual reality technology tools for Dongba script cultural heritage promotion / Liang Xin, Profesor Madya Ts. Dr. Azhari Md Hashim and Li Wen Feng - Liang, Xin; Md Hashim, Azhari; Li, Wen Feng (Universiti Teknologi MARA, Kedah, 2024)
The pictographic Dongba script is a traditional script that is used by the Naxi people in Lijiang, Yunnan Province, in China. Despite being a cultural heritage, it is not actively promoted causing its depletion to continue. The purpose of this study is to discuss and identify the non-individual characters in the Dongba script, as well as to investigate the dynamic approaches to promote them. The study has used a qualitative research approach to discover the characteristics of the Dongba script's non-individual characters utilising the 'composition element', which is the smallest unit of script composition. This study's findings demonstrated that non-individual characters might be created and used, and cultural heritage can be broadly promoted through virtual technologies, including AR animation and digital museums. Significantly, this study offered a model for the future promotion of Dongba script non-individual characters.